Tandem Organic Solar Cells with 18.7% Efficiency Enabled by Suppressing the Charge Recombination in Front Sub‐Cell - Liu, Gongchu; Xia, Ruoxi; Huang, Qiri; Zhang, Kai; Hu, Zhicheng; Jia, Tao; Liu, Xiang; Yip, Hin‐Lap; Huang, Fei (Advanced functional materials, 2021)
The maximum photocurrent in tandem organic solar cells (TOSCs) is often obtained by increasing the thicknesses of sub‐cells, which leads to recombination enhancement of such devices and compromises their power conversion efficiency (PCE). In this work, an efficient interconnecting layer (ICL) is developed, with the structure ZnO NPs:PEI/PEI/PEDOT:PSS, which enables TOSCs with very good reproducibility. Then, it is discovered that the optimal thickness of the front sub‐cell in such TOSCs can be reduced by increasing the proportion of a non‐fullerene acceptor in the active layer. The non‐fullerene acceptor used in this work has a much larger absorption coefficient than the donor in the front sub‐cell, and the absorption reduction of donor can be well complemented by that of the acceptor when increasing the acceptor proportion, thus leading to a significant overall absorption enhancement even with a thinner film. As a result, the optimal thickness of the front sub‐cell is reduced and its charge recombination is suppressed. Ultimately, the use of this ICL combined with fine‐turning of the composition in the front sub‐cell enables an efficient TOSC with a very high fill factor of 78% and an excellent PCE of 18.71% (certified by an accredited institute to be 18.09%) to be obtained. An effective strategy to simultaneously obtain high photocurrent and fill factor in tandem organic solar cells is presented. By increasing the proportion of the non‐fullerene acceptor with strong absorption in the front sub‐cell, maximum photocurrent can be obtained without significantly increasing the thickness of the front sub‐cell, thus ensuring a high fill factor and high photocurrent in device, with a power conversion efficiency over 18%.